AMERICAN SUBCULTURE: AN IDENTITY TRANSFORMATION OF HIP HOP - Ramadhan, Luthfadery (Pengkajian Amerika, Universitas Gadjah Mada, 2023)
Hip-hop has become a global phenomenon, transcending cultural boundaries and influencing artists and communities worldwide. It came from the Black community’s idea of creativity concerning their lifestyle and how they dress—starting from their youth’s energy of creativity to represent their community identity in a larger dominant culture of the US. It transforms the identity of the Black people community into a hip-hop subculture. Through literature analysis, the process of breaking all the challenges and contradictions from the mainstream culture is explained in this paper. Moreover, Burke’s social identity theory and identity theory are utilized in this research. Identity transformation of hip hop to a subculture cannot be separated from its core elements, i.e., music with its poetic and rhyme wordings, unique fashion to emphasize their presence in society, dance as the platform of freedom activity, and language as the tool to convey their identity. These elements are the core of hip-hop in forming self-identities and collective identity, as well as providing a platform for self-expression, storytelling, and cultural exchange.